Molecular epidemiology and carbapenem resistance characteristics of Acinetobacter baumannii causing bloodstream infection from 2009 to 2018 in northwest China - Yihai Gu; Yihai Gu; Wei Zhang; Jine Lei; Lixia Zhang; Xuan Hou; Junqi Tao; Hui Wang; Minghui Deng; Mengrong Zhou; Rui Weng; Jiru Xu (Frontiers in Microbiology, 2022)
Bloodstream infection (BSI) caused by Acinetobacter baumannii poses a serious threat to health and is correlated with high mortality in patients with hospital-acquired infections, so the molecular epidemiology and antimicrobial resistance characteristics of this pathogen urgently need to be explored. A. baumannii isolates from BSI patients were collected in three tertiary hospitals in northwest China from 2009 to 2018. Antimicrobial susceptibility testing was used to determine the MICs of the A. baumannii isolates. Whole-genome sequencing based on the Illumina platform was performed for molecular epidemiological analyses and acquired resistance gene screening. The efflux pump phenotype was detected by examining the influence of an efflux pump inhibitor. The expression of efflux pump genes was evaluated by RT-PCR. In total, 47 A. baumannii isolates causing BSI were collected and they presented multidrug resistance, including resistance to carbapenems. Clone complex (CC) 92 was the most prevalent with 30 isolates, among which a cluster was observed in the phylogenetic tree based on the core genome multi-locus sequence type, indicating the dissemination of a dominant clone. BSI-related A. baumannii isolates normally harbour multiple resistance determinants, of which oxacillinase genes are most common. Except for the intrinsic blaOXA-51 family, there are some carbapenem-resistant determinants in these A. baumannii isolates, including blaOXA-23, which is encoded within the Tn2006, Tn2008 or Tn2009 transposon structures and blaOXA-72. The transfer of blaOXA-72 was suggested by XerC/D site-specific recombination. The AdeABC efflux pump system contributed to carbapenem resistance in A. baumannii isolates, as evidenced by the high expression of some of its encoding genes. Both the clone dissemination and carbapenem resistance mediated by oxacillinase or efflux pumps suggest an effective strategy for hospital infection control.